Land Reform: An Analysis of Definitions, Types and Approaches - Tarisayi, Kudzayi Savious (Asian Journal of Agriculture and Rural Development, 2014)
There is a surfeit of literature on land reforms in various developing countries. Whilst most of the existing literature has principally concentrated on the analysis of examples of land reforms in recent years, there is a paucity of literature detailing what really entails the concept of land reform. Most scholars and development agencies are concentrating on the success or lack thereof, of land reforms without interrogating the concept of land reform. An analysis of what constitutes land reform facilitates further analysis of the success of examples of land reforms around the world. In this paper the researcher gives an overview of the concept of land reform and its various approaches as applied in various parts of the world. Examples will be drawn from countries that have implemented land reforms in recent years, without necessarily interrogating their successes or lack thereof.